The Potential of Familial and School Curriculum-Making Worlds in Teacher Education - Huber, Janice; Farmer, Joanne; Reid, Nathalie; Desrochers, Claire; Mckenzie-Roblee, Sue (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2016)
Diversity, equity, and justice are vital focuses in teacher education programs and research. Yet, studies show that as children and families interact with schools their lives are often ignored, silenced, or used to define them as deficit. This paper inquires into the interactions between early career teachers, children, and families. Using a semi-structured interview protocol, we explored the personal and professional situations 20 early career teachers described as shaping the knowledge they draw on in their interactions with families. Thinking narratively with the stories shared by one teacher, we explore the potential of familial and school curriculum-making worlds in teacher education and ways these understandings may open spaces and conversations that strengthen the interactions between early career teachers and families.